Celebrating 150 years of analyzing fertility trends in Germany - Michael J. Kendzia; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2012)
Ever since the very beginning of the Journal of Economics and Statistics, population economics has featured prominently in the Journal. Fertility naturally plays an important role in population economics. Its size has decreased significantly from the 1900s. Long time-series regarding fertility and basic trends in Germany are documented and analyzed. We identify three different explanatory approaches for the decline in fertility, according to which the various articles of the Journal related to this area are categorized. The paper also investigates previous fertility studies published by the Journal since the beginning. It points out that several articles anticipated subsequent research directions in the area of population economics at an early stage. In addition, significant contributions were made in terms of further developing existing knowledge. Thus, the Journal has helped to expand the research area of population economics.
urn:nbn:de:101:1-201205026319
Keywords: J10; J11; J13; 330; fertility; total fertility rate; Malthus; self-regulation; Q-Q trade-off; Fruchtbarkeit; Demographie; Bevölkerungsökonomie